Evaluation of the Maternal Death Surveillance and Response System, Sierra Leone, 2019 - Kadijatu Nabie Kamara; Adel Hussein Elduma; Joseph Sam Kanu; James Sylvester Squire; Gebrekrstos Negash Gebru (Journal of Interventional Epidemiology and Public Health)
Introduction: Sierra Leone has one of the world's highest maternal mortality ratios (1,120 per 100,000 live births in 2017). It implemented the Maternal Death Surveillance and Response (MDSR) system in 2016 to track maternal deaths in real time. We evaluated the system's effectiveness by assessing key surveillance attributes.